Accessing the Two‐Electron Charge Storage Capacity of MnO2 in Mild Aqueous Electrolytes. Issue 23 (4th May 2020) - Mateos, Mickaël; Makivic, Nikolina; Kim, Yee‐Seul; Limoges, Benoît; Balland, Véronique
Abstract: Rechargeable batteries based on MnO2 cathodes, able to operate in mild aqueous electrolytes, have attracted attention due to their appealing features for the design of low‐cost stationary energy storage devices. However, the charge/discharge mechanism of MnO2 in such media is still a matter of debate. Here, an in‐depth quantitative spectroelectrochemical analysis of MnO2 thin‐films provides a set of unrivaled mechanistic insights. A major finding is that charge storage occurs through the reversible two‐electron faradaic conversion of MnO2 into Mn 2+ in the presence of a wide range of weak Brønsted acids, including the [Zn(H2 O)6 ] 2+ or [Mn(H2 O)6 ] 2+ complexes present in aqueous Zn/MnO2 batteries. Furthermore, it is shown that buffered electrolytes loaded with Mn 2+ are ideal to achieve highly reversible conversion of MnO2 with both high gravimetric capacity and remarkably stable charging/discharging potentials. In the most favorable case, a record gravimetric capacity of 450 mA·h·g −1 is obtained at a high rate of 1.6 A·g −1, with a Coulombic efficiency close to 100% and a MnO2 utilization of 84%. Overall, the present results challenge the common view on MnO2 the charge storage mechanism in mild aqueous electrolytes and underline the benefit of buffered electrolytes for high‐performance rechargeable aqueous batteries. Abstract : By unraveling the charge storage mechanism of MnO2 cathodes in various aqueous electrolytes and the exact role of weak Brønsted acids and bases, the present study demonstrates that buffered electrolytes enable a benefit to be realized from the 2‐electron high gravimetric capacity and high reversibility of the fast MnO2 to Mn 2+ conversion reaction under non‐corrosive conditions.